An epidemiologic profile of trauma patients admitted to maputo central hospital, maputo-mozambique. (7th October 2012) - Mahoque, R; Cliff, J; Lynch, C; Wright, D; Click, L; Sasser, S; Macleod, J
Abstract : Background: In Mozambique, the magnitude of trauma and violence has increased in recent years with traffic crashes as the leading cause of traumatic death. Objective: Is to describe the epidemiological profile of trauma patients hospitalised in the Maputo Central Hospital (HCM), Mozambique. Methods: Descriptive cross-sectional study of injured patients admitted to HCM in 35-day period of study. Results: Injury was frequent in males (65%) 15–34 years old. Traffic accidents were the main cause of injury (39%) with pedestrians most affected, followed by falls (23%) and burns (20%). Majority of falls (64%) occurred over 45 years. Majority of burn victims were under 5 years caused by hot liquid. More than half patients arrived in the hospital in a private car and only 26% received first-aid in lower health facilities, prior to arrival at the hospital. The traffic injured patients required in average 5 days of hospitalisation, while burned required an average of 10 days. Conclusions: Injured patients are primarily men aged 15–34. Road traffic injuries, falls and burns dominate the admitted injuries. Road traffic injured patients were primarily pedestrians. Burns have the highest average length of stay affecting mainly patients under five years of age. Significance: To contribute for national health system strengthening plan and monitory.